2011
DOI: 10.1124/mol.111.073726
|View full text |Cite
|
Sign up to set email alerts
|

The Pharmacological Profile of Brain Liver Intestine Na+ Channel: Inhibition by Diarylamidines and Activation by Fenamates

Abstract: The brain liver intestine Na ϩ channel (BLINaC) is a member of the degenerin/epithelial Na ϩ channel gene family of unknown function. Elucidation of the physiological function of BLINaC would benefit greatly from pharmacological tools that specifically affect BLINaC activity. Guided by the close molecular relation of BLINaC to acid-sensing ion channels, we discovered in this study that rat BLINaC (rBLINaC) and mouse BLINaC are inhibited by micromolar concentrations of diarylamidines and nafamostat, similar to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 41 publications
2
34
0
Order By: Relevance
“…This explains why blockade of Deg/ENaC by amiloride is sensitive to voltage (18,46). A recent study reported that amiloride senses ϳ35% of the electric field across BLINaC (39). Whereas interpretation of such a finding is complicated and often dependent on variables that have not been fully quantified, a simple explanation is that the amiloride binding site or the inhibitory effector site for the cationic guanidinium moiety of amiloride lies about a third of the way through the BLINaC pore referenced from its extracellular mouth.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…This explains why blockade of Deg/ENaC by amiloride is sensitive to voltage (18,46). A recent study reported that amiloride senses ϳ35% of the electric field across BLINaC (39). Whereas interpretation of such a finding is complicated and often dependent on variables that have not been fully quantified, a simple explanation is that the amiloride binding site or the inhibitory effector site for the cationic guanidinium moiety of amiloride lies about a third of the way through the BLINaC pore referenced from its extracellular mouth.…”
Section: Discussionmentioning
confidence: 93%
“…Whole cell macroscopic current recordings of BLINaC expressed in CHO cells also were performed under voltage clamp conditions with standard methods (24,39). Mutant BLINaC harboring the A443T substitution is constitutively active (24).…”
Section: Methodsmentioning
confidence: 99%
“…They are potently inhibited by diarylamidines, a class of anti-protozoal molecules and the related substance nafamostat. 29 Apparent affinity of BASIC for diarylamidines and nafamostat is in the low micromolar range and similar for mouse, rat, and human BASIC. 29 Diarylamidines and nafamostat likely function as pore blockers as their block is voltage-dependent and they compete with amiloride for its binding site, 29 which is in the pore region.…”
Section: Pharmacological Characteristics Of Basicmentioning
confidence: 96%
“…Furthermore, the UDCA-induced current could be inhibited by 10 M diminazene (Fig. 6D), a potent inhibitor for rBASIC (32). WT rBASIC expressed in Xenopus oocytes is characterized by unselectivity for monovalent cations, a rather uncommon feature of Deg/ENaC channels (17).…”
Section: Patch Clamp Recordings From Hek293 Cells Confirm Biophysicalmentioning
confidence: 99%